Formulation and In-Vitro Evaluation of Darifenacin Hydrobromide as Buccal Films - Abbas, Ishraq k.; A. Rajab, Nawal; A. Hussein, Ahmed (Iraqi Journal of Pharmaceutical Sciences, 2019)
Darifenacin hydrobromide (DH) is the more recent uroselective M3 receptor antagonist for treating uncomplicated overactive bladder (OAB). This study was aimed to formulate DH as fast dissolving buccal films (FDBFs) using a solvent casting method to enhance patient’s compliance. Films were prepared by using polyvinyl alcohol (PVA) as a film forming polymer. Different types and concentrations of superdisintegrants (croscarmellose sodium, sodium starch glycolate, indion 414) were used to select the best formula by studying the physicochemical properties of the films, disintegration time (DT) and percent drug release. The results revealed that formula (F9) that containing 7.5mg DH, 2%w/v PVA, 30%w/w glycerol, 0.5%w/v tween 80, 4%w/w indion 414 was the preferred formula. F9 showed the shortest in-vitro disintegration time (31.28sec). In-vitro dissolution profile showed the lowest T80% of the drug in 3.05 min and the highest release of the drug (94%) within 5 min (D5min %). It was concluded that the FDBFs of DH could be considered as a promising drug delivery system with an enhanced disintegration and dissolution rate and better patient compliance.